Paranoia, linguistic ambivalence and erotic sexuality as postmodern techniques in K. Sello Duiker’s the quiet violence of dreams (2020)
African literature in the twenty-first century still projects a robust trail of postcolonial discourses, strongly tied with African thematic refrains, and aptly foregrounded by the agency of postcolonialism. However, there has been an insurrection of stylistic changes from African writers as far as back as the twentieth century, among which is K. Sello Duiker. This study engages Duiker’s deviation from the social realist style of writing, given the fact that Duiker’s renowned novel, The Quiet Violence of Dreams, strongly identifies with postmodern literary trends. Therefore, this essay attempts at critical analysis of paranoia, linguistic ambivalence and erotic sexuality in the novel, with the view to foregrounding its symmetrical stance with postmodernism within African context. One argues further that the novel cannot be restricted to a distinct narrative or interpretation, which stems from the overexploitation of postcolonial themes.